2016
DOI: 10.1097/qai.0000000000000948
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the Negative Effects of Internalized HIV-Related Stigma on Antiretroviral Therapy Adherence in Women

Abstract: Background Internalization of HIV-related stigma may inhibit a person’s ability to manage HIV disease through adherence to treatment regimens. Studies, mainly with white men, have suggested an association between internalized stigma and sub-optimal adherence to antiretroviral therapy (ART). However, there is a scarcity of research with women of different racial/ethnic backgrounds and on mediating mechanisms in the association between internalized stigma and ART adherence. Methods The Women’s Interagency HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
127
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 62 publications
(71 reference statements)
10
127
3
3
Order By: Relevance
“…In addition, the study did not have a large proportion of minority women and thus may not be representative of the populations currently living with and at high risk of acquiring HIV. Minority women in the US are disproportionately affected by HIV, 27 have distinct historical bases for medical distrust, 28 and may experience effects of HIV-related stigma in greater magnitude, 29 compared to non-minority groups. Thus, studies addressing this gap in the literature on the association between perceived discrimination in healthcare settings and ART adherence should include samples with a large proportion of minority women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the study did not have a large proportion of minority women and thus may not be representative of the populations currently living with and at high risk of acquiring HIV. Minority women in the US are disproportionately affected by HIV, 27 have distinct historical bases for medical distrust, 28 and may experience effects of HIV-related stigma in greater magnitude, 29 compared to non-minority groups. Thus, studies addressing this gap in the literature on the association between perceived discrimination in healthcare settings and ART adherence should include samples with a large proportion of minority women.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of depression have consistently been shown to impact HIV medication (ART) adherence across populations. 29,32 According to our conceptual model, perceiving discrimination in healthcare settings may contribute to symptoms of depression—including fatigue, diminished ability to concentrate, and feelings of worthlessness—ultimately impacting the ability of individuals perceiving discrimination to adhere to complex medication regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses document that mental health and substance use disorders are prevalent among disabled PLWHA who had Medi-Cal insurance prior to the enactment of the ACA. It is important to address these conditions, which are major barriers to remaining in treatment for HIV, achieving viral suppression, and returning to employment (Arns, Martin, & Chernoff, 2004; Gonzalez, Batchelder, Psaros, & Safren, 2011; Holtzman et al, 2015; Huynh, Kinsler, Cunningham, & Sayles, 2013; Lucas, 2011; Magidson, Blashill, Safren, & Wagner, 2015; Turan et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…These plans provide more limited access to mental health and substance use treatment than the Ryan White program, which provides to uninsured and underinsured PLWHA a comprehensive range of services that are not provided by any other source (Cahill, Mayer, & Boswell, 2015; Leibowitz et al, 2013). Thus, PLWHA may need to depend on either community providers or wrap-around services from the Ryan White program to support continued engagement in care with the goal of viral suppression (Arns et al, 2004; Cahill et al, 2015; Gonzalez et al, 2011; Holtzman et al, 2015; Huynh et al, 2013; Lucas, 2011; Magidson et al, 2015; Turan et al, 2016). Indeed, a recent study found that post-ACA enrollees in Kaiser Permanente Northern California were more likely to be virally suppressed than a similar group enrolled prior to the ACA (Satre et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increase in older women (age 50+) living with HIV (OWLH), little is known about the psychosocial factors that impact how they live, cope, and age with HIV. Unlike social determinants of health, psychosocial factors are viewed as being amenable to change, resulting in decreased transmission and improved health and thus lessening the burden of AIDS among PLWH [410]. Factors such as healthcare utilization, sexual health, stigma, isolation, loneliness, depression, and substance use impact adherence to HIV medications and clinical outcomes in PLWH in general [1117], but have not been well studied in OWLH.…”
Section: Introductionmentioning
confidence: 99%